The key role of muscle spindles in the pathogenesis of myofascial trigger points according to ramp-and-hold stretch and drug intervention in a rat model - Liu, Lin; Liu, Shi-Xuan; Huang, Qiangmin; Liu, Qing-Guang (Frontiers in Physiology, 2024)
This study investigated whether abnormal peak inverted spontaneous potentials (PISPs) recorded at resting myofascial trigger points (MTrPs) stem from the discharge of muscle spindles. Forty-eight male Sprague-Dawley rats were randomly divided into six groups. Five groups underwent MTrP modeling intervention, whereas one group did not receive intervention and was duly designated as the blank control. After model construction, five rat models were randomly subjected to ramp-andhold stretch tests, succinylcholine injection, eperisone hydrochloride injection, saline injection, and blank drug intervention. By contrast, the rats in the blank control group were subjected to ramp-andhold stretch tests as a control. Frequencies and amplitudes of PISPs were recorded pre-and postinterventions and compared with those of the blank group. Stretch tests showed that the depolarization time and amplitude of PISPs ranged from 0.4 ms to 0.9 ms and from 80 uV to 140 μ V, respectively. However, no PISPs were observed in the control rats. The frequency of PISPs in the ramp and hold phases and the first second after the hold phase was higher than that before stretching (p<0.01). Succinylcholine and eperisone exerted excitatory and inhibitory effects on PISPs, respectively. In the group injected with 0.9% saline, no considerable differences of the PISPs were observed during the entire observation period. In conclusion,PISPs recorded at resting MTrPs are closely related to muscle spindles. The formation of MTrPs may be an important factor that regulate dysfunctional muscle spindles.